Artificial Intelligence-Moderated Gamification Apps: Elevating Gen Z’s English Vocabulary Mastery - Shella Gherina Saptiany; Syamsul Hadi; Benedectta Arsenia Nanda Hardian; Muhammad Madchan Nashir (STAI Hubbulwathan Duri, 2024)
Generation Z students are increasingly adopting gamification in language learning, often enhanced by Artificial Intelligence (AI). Gamified language learning applications are touted for their ability to improve vocabulary acquisition effectively. This study aimed to evaluate the efficacy of AI-assisted gamification in vocabulary learning among Generation Z students in Semarang, Indonesia. A descriptive cross-sectional survey design was employed, involving 400 participants. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) to identify the effectiveness of gamified applications and their components in vocabulary acquisition. The findings revealed that gamified vocabulary instruction using AI-assisted applications is highly effective. Specifically, AI applications demonstrated rapid impacts on learning outcomes, while gamified computer software required less sustained effort. However, the synergistic use of both technologies showed no significant additional improvement in learning outcomes. Key gamification elements such as avatars, badges, points, leaderboards, feedback, and storytelling were analyzed. Among these, game components, including avatars and badges, had the strongest influence on vocabulary acquisition. The study underscores the effectiveness of gamified applications in vocabulary learning among Generation Z, with a particular emphasis on the contribution of AI. While both AI and gamification independently enhance learning, their combined use does not yield a noticeable synergistic effect. The prominent role of game components suggests their prioritization in designing gamified educational tools. AI-assisted gamified language learning applications are effective for vocabulary acquisition, with game components playing a pivotal role. Future research should explore the long-term implications of integrating AI and gamification for sustained learning outcomes.